COMPARATIVE ANALYSIS OF TECHNOLOGICAL EQUIPMENT RESEARCH METHODS ON THE EXAMPLE OF FORCE CALCULATION OF THREAD TAKE-UP LEVERS OF LOCKSTITCH SEWING MACHINES - МАНОЙЛЕНКО, О. П.; ДВОРЖАК, В. М.; ГУДИМ, А. Г.; ШКВИРА, В. В.; ГРИЦАЙ, І. В. (Technologies and Engineering, 2023)
Purpose of the work consists in a comparative analysis of classical methods of dynamics when researching lever mechanisms using applied CAD/CAE programs and methods of solid-state computer 3D modeling, establishing the reliability of the research results and the feasibility of using a computer experiment in engineering analysis. Methodology of research is based on the apparatus of vector algebra; analytical methods of kinetostatic calculation of flat hinge-lever mechanisms; methods of solid-state computer 3D modeling using CAD/CAE systems. Findings: diagrams of the maximum values of reactions in kinematic pairs (KP) of the thread take-up lever mechanism depending on the rotation frequency of the main shaft were obtained, and the relative error of the values of the maximum reactions in the KP of the mechanism, which were obtained analytically and by the method of computer solid-state simulation 3D modeling, was determined. Originality consists in the comparison of the methods of kinetostatic calculation and computer simulation modeling of hinge-lever mechanisms, the relative accuracy of the obtained results of the reaction values in the KP was determined by independent methods, and the relevance of the use of a computer experiment in engineering analysis with the use of CAD/CAE systems was proven. Practical value of the work consists in the use of the obtained research results for the modernization or development of new lockstitch sewing machine mechanisms and the feasibility of using virtual solid-state 3D models in engineering analysis for kinematic and force calculations of lever mechanisms.